Door to the Mediterranean: port activity in late Islamic Lisbon - Miranda, Ana (2019)
By the time we arrived there, it was the most opulent commercial centre of all Africa and a big part of Europe” attested to in his report an English crusader who had participated in the Christian conquest of Lisbon, in the middle of the 12th century1 . Despite a sincere feeling of wonder the crusader might have experienced, one cannot ignore some exaggeration due perhaps, to the wish for exalting a recent prey. Nonetheless, in this narrative of the conquest of Lisbon, De Expugnatione Lyxbonensi, it stands clear the connotation of this city with a civilizational archetype distinctive from the northern European one.